Analysis of Determining Service Products for Soekarno Hatta Airport Terminal 3 - Sanjaya, Hendri Aka; Unggu, Winneth Tamake; Simarmata, Juliater (Dinasti International Journal of Management Science, 2024)
The analysis article for determining service products at Soekarno Hatta Airport Terminal 3 is a scientific literature review article within the scope of marketing management science. The purpose of writing this literature article is to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methods were applied in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was obtained from credible academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and reputable journals. The findings of this research are as follows: 1) Market needs influence the determination of service products at Terminal 3 of Soekarno Hatta Airport; 2) Market trends influence the determination of service products at Terminal 3 of Soekarno Hatta Airport; and 3) Branding influences the determination of service products at Terminal 3 of Soekarno Hatta Airport.